Slovenia : Technical Assistance Report-Bank Intervention and Resolution and the Deposit Guarantee System. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report assesses the bank resolution framework and deposit guarantee system in Slovenia. There are three necessary requirements for effective bank resolution: (1) a special bank resolution regime, (2) advance preparation for bank intervention and resolution, and (3) an adequately funded Deposit Guarantee Scheme (DGS). Slovenia's banking law provides for the first, while the recommendation to create a Resolution Unit within Bank of Slovenia has been adopted. The extant DGS, however, is an ex post funded scheme that does not fulfill the third criteria. Slovenia must implement the European Union Deposit Guarantee Scheme Directive into national law, which calls for an ex ante funded DGS.